The Kidney Donor Profile Index (KDPI) of Marginal Donors Allocated by Standardized Pretransplant Donor Biopsy Assessment: Distribution and Association With Graft Outcomes. Issue 11 (25th August 2014) - Gandolfini, I.; Buzio, C.; Zanelli, P.; Palmisano, A.; Cremaschi, E.; Vaglio, A.; Piotti, G.; Melfa, L.; La Manna, G.; Feliciangeli, G.; Cappuccilli, M.; Scolari, M. P.; et al.
Abstract Pretransplant donor biopsy (PTDB)‐based marginal donor allocation systems to single or dual renal transplantation could increase the use of organs with Kidney Donor Profile Index (KDPI) in the highest range (e.g. >80 or >90), whose discard rate approximates 50% in the United States. To test this hypothesis, we retrospectively calculated the KDPI and analyzed the outcomes of 442 marginal kidney transplants (340 single transplants: 278 with a PTDB Remuzzi score <4 [median KDPI: 87; interquartile range (IQR): 78–94] and 62 with a score = 4 [median KDPI: 87; IQR: 76–93]; 102 dual transplants [median KDPI: 93; IQR: 86–96]) and 248 single standard transplant controls (median KDPI: 36; IQR: 18–51). PTDB‐based allocation of marginal grafts led to a limited discard rate of 15% for kidneys with KDPI of 80–90 and of 37% for kidneys with a KDPI of 91–100. Although 1‐year estimated GFRs were significantly lower in recipients of marginal kidneys (−9.3, −17.9 and −18.8 mL/min, for dual transplants, single kidneys with PTDB score <4 and =4, respectively; p < 0.001), graft survival (median follow‐up 3.3 years) was similar between marginal and standard kidney transplants (hazard ratio: 1.20 [95% confidence interval: 0.80–1.79; p = 0.38]). In conclusion, PTDB‐based allocation allows the safe transplantation of kidneys with KDPI in the highest range that may otherwise be discarded.